Railways Galicia Austro-Hungarian period: historiography of the problem - Dymytryuk, V. M. (History of science and technology, 2016)
The article presents historiography of «Roads Galicia in Austro-Hungarian period» problem. The study of marked problem required searching and studying a substantial part of sources, which are stored in the archives and libraries of Chernivtsi, Lviv, Moscow and St. Petersburg. Of course, main part of factual material is drawn from archives of Chernivtsi regional state archive, book and newspaper Funds of the Scientific library of Chernivtsi University and the Lviv State Regional Archive.